Physiology - Costanzo, Linda S. (Saunders Elsevier, 2006)
Featuring a focus on mechanisms, this popular reference comprehensively covers important concepts in physiology, both at the organ system and cellular levels. Easy to read and user-friendly, the revised third edition stresses essential and relevant content with absolute clarity and includes concise step-by-step explanations complemented by numerous tables and abundant illustrations. It provides information on the underlying principles of cellular physiology, the autonomic nervous system, and neurophysiology, as well as the cardiovascular, respiratory, renal, acid-base, gastrointestinal, endocrine, and reproductive organ systems.